Capacity Analysis of Coastal Abrasion Disasters in North Galesong District, Takalar - Firdaus, Firdaus; Chaerul, Muhammad; Gusty, Sri (Jurnal Kewarganegaraan, 2022)
AbstractCommunity capacity is closely related to disaster risk reduction efforts, consisting of mitigation, preparedness and survival capabilities. This study aims to determine the level of capacity against coastal abrasion disasters in North Galesong District. The analytical method used is the coastal abrasion disaster risk capacity index which consists of regulations, institutions, early warning systems, disaster mitigation efforts and preparedness. The results showed that overall, the villages in the coastal area of North Galesong District were included in the low capacity category. The low category capacity level represents the low ability of the region and the community to take action to reduce the level of threat and level of losses due to coastal abrasion disasters.Keywords: Capacity, Mitigation, Disaster, Coastal Abrasion, North Galesong